Influência do ciclo de füração na usinabilidade do ferro fundido cinzento GH190 - Silva, Hélio Antônio da (2010)
Among the machining operations, drilling with twist drills stands out as one of the most widely used in the metalworking industry. Although the literature presents a lot of research, surely there is still room for scientific work on the drilling process. This study examines the influence of the drilling cycle (continuous and intermittent - popularly known as "pecker" or " eliminates chip") on the performance of machining of cast iron GH - 190 with HSS twist drills coated with multilayer TiN-TiAlN, diameter 10 mm. The experiments were based on a fractional factorial design 24-1. The trials were organized in two parts, first with the retrieve of the tool of 1 mm and one, two and three stops of the tool. The second part with three stops along the length of drilling and tool retrieves of 1 mm, 3 mm and total. Each test was performed in three runs, one test and two replicas. The end of tool life criterion adopted was catastrophic failure of the tool (collapse). Besides the tool life, the following output variables were also considered: the surface finish, the cylindricity deviation, roundness, thrust force (Fz) and torque (Mz) monitored. During the tests images of the cutting edge, cutting point and margin of the drills were recorded to check the levels of wear. Different cutting speeds (45 m / min and 65 m / min), feed rates (0.20 mm / rev and 0.30 mm / rev) and lubri-coolant conditions (dry, flood and MQF) were used. For comparison purposes, ten plans with eight trials each, were combined and analyzed. The results showed that the drilling cycle affects machinability, depending upon the lubri-cooling system and the number of stops used. The cutting speed, the flood and MQF systems are the variables that most influenced the tool. In general there was a direct relationship between cutting conditions and the output variables: thrust force, torque, surface roughness (Ra and Rz) and geometric deviations (roundness and cylindricity). The action of cutting fluids contributes to better surface quality of machined holes.